2012
DOI: 10.1186/cc11160
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support and brain tissue glucose metabolism in poor-grade SAH: a retrospective observational study

Abstract: IntroductionWe sought to determine the effect of nutritional support and insulin infusion therapy on serum and brain glucose levels and cerebral metabolic crisis after aneurysmal subarachnoid hemorrhage (SAH).MethodsWe used a retrospective observational cohort study of 50 mechanically ventilated poor-grade (Hunt-Hess 4 or 5) aneurysmal SAH patients who underwent brain microdialysis monitoring for an average of 109 hours. Enteral nutrition was started within 72 hours of admission whenever feasible. Intensive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
3
19
2
Order By: Relevance
“…The primary target for each patient was (or ) and the primary caloric source was Osmolite. The NICU population does receive insulin; how and why is complex and is discussed in detail in Schmidt et al [27]. We do not attempt to control for insulin because it is difficult to foresee whether it matters; our results will show that the insulin regimen in the NICU population does not affect our results to first order in statistical moment (i.e., the mean).…”
Section: Methodsmentioning
confidence: 85%
“…The primary target for each patient was (or ) and the primary caloric source was Osmolite. The NICU population does receive insulin; how and why is complex and is discussed in detail in Schmidt et al [27]. We do not attempt to control for insulin because it is difficult to foresee whether it matters; our results will show that the insulin regimen in the NICU population does not affect our results to first order in statistical moment (i.e., the mean).…”
Section: Methodsmentioning
confidence: 85%
“…Recently, reports on comatose patients with subarachnoid hemorrhage have shown conflicting results. Schmidt et al (2012) failed to demonstrate an association between nutrition therapy and improvement of brain glucose. In parallel, they showed that insulin was associated with reductions in brain glucose independent of serum glucose (Schmidt et al, 2012).…”
Section: Brain Metabolic Patterns and Optimization Of Substrate Supplymentioning
confidence: 99%
“…Schmidt et al (2012) failed to demonstrate an association between nutrition therapy and improvement of brain glucose. In parallel, they showed that insulin was associated with reductions in brain glucose independent of serum glucose (Schmidt et al, 2012). On the other hand, Kofler et al (2018) recently found significant increases in CMD-glucose levels, independent of the baseline brain metabolic profile and insulin administration.…”
Section: Brain Metabolic Patterns and Optimization Of Substrate Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…The requirements increase over time: Throughout this period the HBE underestimates BEE calculations as compared with indirect calorimetry (IC). [52] Recent brain microdialysis studies have shown that after subarachnoid haemorrhage, over time, the interstitial milieu becomes hyperglycolytic and cerebral glucose consumption increases. Enteral nutrition and insulin administration to control plasma glucose levels may increase metabolic stress in these patients by causing brain interstitial hypoglycaemia and increase in lactate and pyruvate levels.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%